The state: a theoretical analysis and empirical observation - Ghazali Mayudin (Universiti Kebangsaan Malaysia, 1980)
This paper attempts to analyse the Marxist theory of the state and relates the theory to the contemporary development of the western industrial countries. The focus of discussion is on two Marxist interpretations of the state i.e. the state as an instrument of the bourgeoisie and the state which has autonomy in its relations with different classes in the society. The debate between Miliband and Poulantzas on the state is also discussed. Another aspect which is discussed is the ability of the Marxist theory of the state to explain the complex changes and developments in the western countries. In his conclusion, the writer emphasizes that the theory fails to provide a satisfactory explanation of the function of the state in contemporary western countries.